Association between serum biomarkers and postoperative delirium after cardiac surgery - Gailiušas, Mindaugas; Andrejaitienė, Judita; Širvinskas, Edmundas; Krasauskas, Darijus; Švagždienė, Milda; Kumpaitienė, Birutė (Acta medica Lituanica, 2019)
Background. In cardiac surgery, patients face an increased risk of developing postoperative delirium (POD) that is associated with poor outcomes. Neuron-specific enolase (NSE) and glial fibrillary acidic protein (GFAP) have shown some promising results as potential tools for POD risk stratification, diagnosis, monitoring, and prognosis. Methods. Prospective single-centre study enrolled 44 patients undergoing elective coronary artery bypass grafting (CABG) and/ or valve procedures using cardiopulmonary bypass (CPB). The patients were assessed and monitored preoperatively, during surgery, and in the early postoperative period. The blood levels of NSE and GFAP were measured before and after surgery. The early POD was assessed by CAM-ICU criteria and patients were assigned to the POD group (with POD) or to the NPOD group (without POD) retrospectively. Results. The incidence of POD was 18.2%. After surgery, NSE significantly increased in the whole sample (p = 0.002). Comparing between groups, NSE significantly increased in the POD group after surgery (p = 0.042). ΔGFAP (before/after operation) for the whole sample was statistically significant (p = 0.022). There was a significant correlation between ΔGFAP and the lowest MAP during surgery in the POD group (p = 0.033). Conclusions. Our study demonstrated that NSE and GFAP are associated with early POD. An increase in NSE level during the perioperative period may be associated with subclinical neuronal damage. Serum GFAP levels show the damage of glial cells. Further studies are needed to find the factors influencing the individual limits of optimal MAP during surgery.